An evaluation of aspects of the PEM (protein energy malnutrition) Scheme for malnourished children in Gauteng Province - Marshall, Carol Anne (My University, 2014)
This study assessed aspects of targeting of the PEM scheme in Gauteng province. This food supplementation scheme targets beneficiaries including children 0-6 years, using largely anthropometric criteria. Routine provincial intervention data was analysed and related to available data cm expenditure, population and indices of socio-economic need. Only 28% were children in the critical 7-36 month age group; and coverage was very low, with no correlation between indices of need and programme implementation by area. An exit interview to a sample of caretakers of 0-6 year old children in four clinics (two Local Authority, two provincial) examined the process of identification of beneficiaries. Low attendance by children over 1 year and 40% errors in growth monitoring, more frequent among sick children, effectively reduced screening coverage among the most at-risk. Health worker misclassification resulted in an 81% exclusion error among those meeting entry criteria, while 4% of the total were wrongly enrolled. Advice and nutrition promotion to caregivers was inadequate. Recommendations include service re-organisation, community-based initiatives and better monitoring.
Keywords: Protein-Energy Malnutrition; Protein Deficiency